The use of mix ration corn-silage based for dairy cattle: A systematic review on methane emission and milk quality - Ainun Nafisah; Nurul Annazhifah; Nezly Nurlia Putri (Jurnal Peternakan, 2023)
In subtropical countries, corn silage is the primary ration for dairy cattle. Corn silage is often chosen in mixed rations because of its higher biomass yield, superior palatability, homogeneous yield quality, and simple silage preparation due to its higher soluble sugar content. The review aimed to (i) compile a list of the different feed components that may be combined with corn silage and (ii) compare the results of their effects on methane gas emissions, milk quality, and feed efficiency as determined by an in vivo approach. Relevant papers indexed in the computerized Scopus database and published in a variety of scientific publications were found. This systematic review was based on the PRISMA. Records included in review from databases (n = 10). This method has been applied by the authors in the articles that have been reviewed. In general, the content of CP and EE in the study was almost the same. CH4 (g/d) is lowest at 315-329, and for CH4 (g/kg of DMI) is 15.7-15.9. Substituting ordinary corn silage with Enogen corn silage (ECS) in TMR can increase milk production (38.8-40.8 kg/d) and milk quality (fat 3.82-4%, protein 3.07-3.11% and lactose 4.86-4.92%). The present literature review confirms that all mixed feeds with corn silage base used have nutrient content  in accordance with the daily nutrient requirements of dairy cattle. Mixed feed that produces the lowest CH4 emissions (g/kg of DMI) and good milk quality is by giving ECS (Enogen corn silage).